THE EFFECT OF LEVERAGE AND ASSET PRICES ON MUTUAL FUND RISK IN MUTUAL FUND COMPANIES IN INDONESIA - Nensy Parabak; Musdalifah Azis (Journal of Management Small and Medium Enterprises (SMEs), 2021)
This study aims to know the effect of Leverage and Asset Prices on Mutual Fund Risk. This research was conducted at equity mutual fund companies listed in OJK for the period 2018-2019. This study used purposive sampling with a total sample of 23 equity mutual funds. The type of data used is quantitative data and the data source is in the form of company annual financial reports. The data analysis tools used were descriptive statistics and panel data regression The results of this study find that mutual fund is managed by an investment manager with high leverage and high asset prices will have a high risk as well, and can be suppressed when the investment manager creates a low level of leverage and a low asset prices. . Keywords: Leverage, Asset Price, and Mutual Fund Risk